Primary malignant melanoma of the esophagus with multiple lymph node metastases: A case report and literature review. Issue 22 (29th May 2020) - Iwasaki, Kenichi; Ota, Yoshihiro; Yamada, Erika; Takahashi, Kosuke; Watanabe, Takafumi; Makuuchi, Yosuke; Suda, Takeshi; Osaka, Yoshiaki; Seshimo, Akiyoshi; Katsumata, Kenji; Tsuchida, Akihiko
Abstract: Rationale: Primary malignant melanoma of the esophagus (PMME) is a very rare malignancy accounting for only 0.1% to 0.2% of all malignant esophageal lesions. Presently, there are no standard strategies or clear guidelines for PMME treatment. Patient concerns: Herein, we report a patient who had PMME with multiple lymph node metastases (LNMs) who was treated successfully by esophagectomy. In March 2018, a 74-year-old man with symptoms of continuous dysphagia was referred to our hospital. Diagnosis: Upper gastrointestinal endoscopic examination revealed melanin pigmentation in the middle thoracic esophagus and a pigmented polypoid mass in the lower esophagus. Histopathological examination of the endoscopic biopsy specimen revealed malignant melanoma. Contrast-enhanced computed tomography showed a 3 cm tumor lesion with several enlarged lymph nodes without distant metastasis. The preoperative diagnosis based on the TNM classification was cT2N2M0 stage III. Interventions: The patient underwent esophagectomy with lymph node dissection. Outcomes: Histopathological examination showed that the tumor extended to the submucosal layer of the esophageal wall, with multiple LNMs. Although multiple LNMs were detected, computed tomography scan 15 months after surgery showed no recurrence. Additionally, we analyzed the relationship between the overall survival and the clinicopathological factors including LNMs in 48 previously reported cases of PMME that were surgically treated. Lessons: To our knowledge, this is the first report on the effect of LNMs on the prognosis of PMME patients. The analysis revealed the prognostic value of the TNM stage. Early tumor detection and esophagectomy with lymph node dissection may play as key factors for achieving a better overall survival of PMME patients.